2008
DOI: 10.1097/meg.0b013e3282f5e9b6
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric endoscopy performed by adult-service gastroenterologists

Abstract: General gastroenterologists supported by paediatricians can provide endoscopic services for children safely and promptly in their local hospital. This is appropriate for the management of common gastrointestinal problems affecting children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
1
13
0
3
Order By: Relevance
“…The indication for endoscopy in our center was carefully considered for each child, and most procedures were performed by pediatric gastroenterologists followed by adult gastroenterologists, which is consistent with a study reported by Hayat et al (3) analyzing pediatric endoscopies in an adult gastroenterology department. Indications for these explorations are usually consistent with those reported in other papers (3,5), with foreign body extraction, caustic ingestion, and duodenal biopsy collection being most common for UDE, and abdominal pain, diarrhea, rectal bleeding, or suspected IBD flare-up for colonoscopy. Despite careful indication selection, endoscopy was normal (i.e., with no endoscopic and/or histological changes in biopsy samples) for 27% of UDEs and 25% of colonoscopies, which represents a lower percentage when compared to a North American series (6) where 44% of UDEs and 41% of colonoscopies yielded normal findings, and a pediatric Australian series (7) where 48% of UDEs were normal.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The indication for endoscopy in our center was carefully considered for each child, and most procedures were performed by pediatric gastroenterologists followed by adult gastroenterologists, which is consistent with a study reported by Hayat et al (3) analyzing pediatric endoscopies in an adult gastroenterology department. Indications for these explorations are usually consistent with those reported in other papers (3,5), with foreign body extraction, caustic ingestion, and duodenal biopsy collection being most common for UDE, and abdominal pain, diarrhea, rectal bleeding, or suspected IBD flare-up for colonoscopy. Despite careful indication selection, endoscopy was normal (i.e., with no endoscopic and/or histological changes in biopsy samples) for 27% of UDEs and 25% of colonoscopies, which represents a lower percentage when compared to a North American series (6) where 44% of UDEs and 41% of colonoscopies yielded normal findings, and a pediatric Australian series (7) where 48% of UDEs were normal.…”
Section: Discussionsupporting
confidence: 64%
“…Under ideal conditions, pediatric endoscopies should be performed by experienced pediatric endoscopists; however, for most patients, as referral to a site with a pediatric dept. including a pediatric endoscopy unit with expertise is challenging and requires wait time, endoscopists at the general gastroenterology dept., working together with pediatricians, eventually perform a high number of endoscopic procedures in children (3).…”
Section: Introductionmentioning
confidence: 99%
“…Also, only a relatively small number of studies have been done in an adult endoscopic suite and these studies had only a small number of patients. 16,17 Besides, the appropriateness of pediatric endoscopy in an adult suite has never been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in very complex procedures, involvement of an experienced endoscopist, even if he/she is not a pediatrician, should be considered. For example, it would be advisable that a pediatrician performs a diagnostic colonoscopy but hands over to a gastroenterologist to perform a polypectomy if required, because this task is very uncommon in children but daily practice in adults [3]. Another example might be the performance of an ERCP or hemostasis techniques in variceal bleeds.…”
Section: Who Should Perform the Procedure?mentioning
confidence: 99%